A secretagogin locus of the mammalian hypothalamus controls stress hormone release. (27th November 2014) - Romanov, Roman A; Alpár, Alán; Zhang, Ming‐Dong; Zeisel, Amit; Calas, André; Landry, Marc; Fuszard, Matthew; Shirran, Sally L; Schnell, Robert; Dobolyi, Árpád; Oláh, Márk; Spence, Lauren; et al.
Abstract A hierarchical hormonal cascade along the hypothalamic‐pituitary‐adrenal axis orchestrates bodily responses to stress. Although corticotropin‐releasing hormone (CRH), produced by parvocellular neurons of the hypothalamic paraventricular nucleus (PVN) and released into the portal circulation at the median eminence, is known to prime downstream hormone release, the molecular mechanism regulating phasic CRH release remains poorly understood. Here, we find a cohort of parvocellular cells interspersed with magnocellular PVN neurons expressing secretagogin. Single‐cell transcriptome analysis combined with protein interactome profiling identifies secretagogin neurons as a distinct CRH‐releasing neuron population reliant on secretagogin's Ca2+ sensor properties and protein interactions with the vesicular traffic and exocytosis release machineries to liberate this key hypothalamic releasing hormone. Pharmacological tools combined with RNA interference demonstrate that secretagogin's loss of function occludes adrenocorticotropic hormone release from the pituitary and lowers peripheral corticosterone levels in response to acute stress. Cumulatively, these data define a novel secretagogin neuronal locus and molecular axis underpinning stress responsiveness.